Comparison of PKRP and TUVP in the treatment of high-risk BPH and analysis of postoperative influencing factors - Song, Yao; Pang, Songqiang; Luo, Gongtang; Li, Sen; He, Yaqiang; Yang, Jinqiang (Frontiers in Surgery, 2022)
Objective: To compare the efficacy of plasma kinetic loop resection of the prostate (PKRP) and transurethral vaporization of the prostate (TUVP) for the treatment of high-risk benign prostatic hyperplasia (BPH) and to analyze the influence of the related factors on the operation of BPH. Methods: A total of 108 patients of high-risk BPH patients diagnosed in our hospital from March 2018 to September 2021 were selected and randomly divided into an observation group and a control group, 54 cases in each group. The control group was treated with TUVP, and the observation group was treated with PKRP. The international prostate symptom score (IPSS), quality of life index (QOL), maximum urine flow rate (Qmax), and residual urine volume (RU) were observed before and after treatment. The general information such as age, educational level, residence and residence status of the patient as well as clinical information such as surgical method, nocturia frequency, preoperative IPSS score, RU, medical history, and prostate texture were also recorded. All patients were followed up for one month and complications were recorded. Results: After treatment, the IPSS score, QOL score and RU of patients in the two groups were lower than those before treatment, and the Qmax was higher than that before treatment (P<0.05). The IPSS score, QOL score and RU of the observation group were lower than those of the control group, and the Qmax was higher than that of the control group (P<0.05). The incidence of postoperative complications in the observation group was lower than that in the control group (P<0.05). Conclusion: PKRP in the treatment of high-risk BPH patients can effectively reduce the IPSS score, QOL score and RU, and significantly increase Qmax, with less complications and good prognosis. His postoperative recovery was related to his age, surgical method, nocturia frequency, preoperative IPSS score, RU, and medical history. Therefore, choosing PKRP to treat high-risk BPH patients can effectively improve the postoperative urethral functional recovery of patients and reduce the occurrence of complications.